2020
DOI: 10.1101/2020.12.23.20248579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Checklist for Assessing the Methodological Quality of Concurrent tES-fMRI Studies (ContES Checklist): A Consensus Study and Statement

Abstract: BackgroundLow intensity transcranial electrical stimulation (tES), including alternating or direct current stimulation (tACS or tDCS), applies weak electrical stimulation to modulate brain circuits. Integration of tES with concurrent functional magnetic resonance imaging (fMRI) allows neuromodulation of brain regions while mapping network functions, therefore supporting causal studies of both brain function and tES effects. The methodology of tES-fMRI studies, including hardware and protocols, underpin any out… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…The development of the ContES checklist by using the Delphi technique involved the following steps: (i) formation of the SC, (ii) selection of the expert panel (EP), (iii) checklist development and revision and (iv) data collection and analysis. The protocol of this study is pre-registered in OSF 66 , and its questionnaires and databases are publicly available in the study's Open Science Framework (OSF) page (https://osf.io/f9j8z/).…”
Section: Methodsmentioning
confidence: 99%
“…The development of the ContES checklist by using the Delphi technique involved the following steps: (i) formation of the SC, (ii) selection of the expert panel (EP), (iii) checklist development and revision and (iv) data collection and analysis. The protocol of this study is pre-registered in OSF 66 , and its questionnaires and databases are publicly available in the study's Open Science Framework (OSF) page (https://osf.io/f9j8z/).…”
Section: Methodsmentioning
confidence: 99%
“…We used a Delphi technique, in which comments and feedback are iteratively discussed (Hsu and Sandford, 2019), for addressing challenges and proposing recommendations for digitizing tES trials. Following recent papers (Ekhtiari et al, 2022a, 2022b), we initially convened a steering committee (SC) group, formed based on the collaborative network of the leading authors, to develop structured questionnaires with items using Five-point Likert scales or open questions (Supplementary Material - Appendix 2). The SC also provided qualitative feedback on several topics that were analyzed by the leading authors and qualitatively described here.…”
Section: Methodsmentioning
confidence: 99%
“…However, tES inside the scanner in consecutive or concurrent approaches requires specific practical considerations [65]. A checklist was recently developed for concurrent tES-fMRI obtained from a Delphi consensus process regarding essential factors that should be checked during a concurrent tES-fMRI trial to ensure transparency, completeness of the report and to improve study replicability and general reporting practice of concurrent tES-fMRI trials [66].…”
Section: Integrating Tes With Fmrimentioning
confidence: 99%
“…This paradigm should be tested experimentally to identify potential confounds of the design. We previously performed a systematic review to propose a checklist for concurrent tES-fMRI experiments [66]. We updated our systematic review by the end of April 2022, and we found that of all currently available tES-fMRI studies, none has used a closed-loop brain stimulation protocol.…”
Section: Closed-loop Tes-fmri Setupmentioning
confidence: 99%